2016
DOI: 10.1021/acs.jpcc.5b12580
|View full text |Cite
|
Sign up to set email alerts
|

Surface on Surface. Survey of the Monolayer Gold–Graphene Interaction from Au12 and PAH via Relativistic DFT Calculations

Abstract: Gold-graphene interaction at the interface is evaluated through different polyaromatic hydrocarbons (PAH), accounted by C 6 H 6 , C 24 H 12 , C 54 H 16 and C 96 H 18 , focusing into different energetic terms related to the overall interaction. Our results characterize the neutral gold-PAH interaction nature with 45% of dispersion character, 35% of electrostatic, and 20% of covalent character, suggesting that moderate van der Waals character is mostly involved in the interaction, which increases according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The phase transition under controlled potential was thus a transition to a metastable adlayer on Au(111). Indeed, according to density functional theory (DFT) calculations for PAH molecules and a Au surface, charge transfer occurs from the Au surface to the PAH molecules, 60 suggesting that the surface charge density can be precisely modulated by the applied potential at the electrochemical interface and appears to contribute not only to the molecule–substrate interaction but also to the interactions among the molecules. PAHs are generally neutral, but they have π electrons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase transition under controlled potential was thus a transition to a metastable adlayer on Au(111). Indeed, according to density functional theory (DFT) calculations for PAH molecules and a Au surface, charge transfer occurs from the Au surface to the PAH molecules, 60 suggesting that the surface charge density can be precisely modulated by the applied potential at the electrochemical interface and appears to contribute not only to the molecule–substrate interaction but also to the interactions among the molecules. PAHs are generally neutral, but they have π electrons.…”
Section: Resultsmentioning
confidence: 99%
“…According to a recent theoretical calculation, PAHs such as hexabenzocoronene adsorb onto the bridge site rather than the top site of the Au atoms in Au 12 clusters. 60 …”
Section: Resultsmentioning
confidence: 99%
“…For the sake of comparison, a previous work has shown that the PAH circumcoronene (C 54 H 18 ) is large enough to model the graphene-Au 12 interaction. 34 2.1.2 Density functional theory and ab initio calculations. Dispersion-corrected density functional theory (DFT) has been applied to study the adsorption of up to 8 O 2 molecules on bare Cu 5 and Cu 5 -Cu 5 systems as well as circumpyrenesupported Cu 5 clusters.…”
Section: Methodsmentioning
confidence: 99%
“…For the sake of comparison, a previous work has shown that the PAH circumcoronene (C 54 H 18 ) is large enough to model the graphene–Au 12 interaction. 34…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation